Respuesta :

Answer:

C. m+n/2

Step-by-step explanation:

Factor out the 3 in the numerator and apply the difference of squares, factor out the 6 in the denominator, and reduce where applicable. It'll all cone out to look like option C.

Ver imagen Percivle

Answer:

C)

[tex] \frac{m + n}{2} [/tex]

Step-by-step explanation:

[tex] \frac{3{m}^{2} - 3 {n}^{2} }{6m - 6n } = \frac{3( {m}^{2} - {n}^{2}) }{3(2m - 2n)} \\ = \frac{ {m}^{2} - {n}^{2} }{2m - 2n} \\ = \frac{(m - n)(m + n)}{2(m - n)} \\ = \frac{m + n}{2} [/tex]

ACCESS MORE